50 kā bihtarīn adab - Jaʻfrī, ʻAlī Sardār, 1913-2000; Panḍit, Prakāsh, 1924- (SAMP early 20th-century Indian books project ;, 1950)
Collection of poems, short stories and articles on Urdu literature published in 1950.